1999
DOI: 10.1002/(sici)1097-4644(19990801)74:2<211::aid-jcb7>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Induction of transcription factor interferon regulatory factor-1 by interferon-? (IFN?) and tumor necrosis factor-? (TNF?) in FRTL-5 cells

Abstract: While it is well known that interferon-gamma (IFN gamma) and tumor necrosis factor-alpha (TNF alpha) play a role in the regulation of thyroid growth and differentiated functions, the cellular and molecular mechanisms involved in mediating the effects of IFN gamma and TNF alpha on thyroid function are unknown. In the present study, we used FRTL-5 rat thyroid cells to examine the effects of IFN gamma and TNF alpha on gene expression of transcription factor interferon regulatory factor-1 (IRF-1), which is involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The lack of a significant association between intratumoral IRF-2 and IFN-g in the examined ovarian cancer samples as well as the fact that IRF-1 and IFN-g were found to be independent of each other in predicting overall survival may substantiate our in vitro-findings and those of others 23,24 showing that the expression of both IRFs is not exclusively regulated by IFN-g, but may be significantly influenced by other locally acting cytokines such as IL-1 and TNF-a, but also by growth factors like EGF. In this context, it should be emphasized that especially IRF-1, as a relevant prognosticator, should not be regarded as a simple secondmessenger of IFN-g, but as a variable that reflects local anti-tumor immune response and other events influencing tumor growth, namely more precisely than does IFN-g.…”
Section: Discussionsupporting
confidence: 86%
“…The lack of a significant association between intratumoral IRF-2 and IFN-g in the examined ovarian cancer samples as well as the fact that IRF-1 and IFN-g were found to be independent of each other in predicting overall survival may substantiate our in vitro-findings and those of others 23,24 showing that the expression of both IRFs is not exclusively regulated by IFN-g, but may be significantly influenced by other locally acting cytokines such as IL-1 and TNF-a, but also by growth factors like EGF. In this context, it should be emphasized that especially IRF-1, as a relevant prognosticator, should not be regarded as a simple secondmessenger of IFN-g, but as a variable that reflects local anti-tumor immune response and other events influencing tumor growth, namely more precisely than does IFN-g.…”
Section: Discussionsupporting
confidence: 86%
“…IRF-1 is induced by a number of stimuli, including IFN-g, TNFa, and LPS, in a variety of cells (37)(38)(39) and is supposed to be an essential transcriptional activator for IFN-g-induced CCL5/ RANTES expression in murine macrophages (40,41). Consistent with previous reports (9,42), costimulation with IFN-g and TNF-a induced CCL5/RANTES production in BEAS-2B cells and was associated with IRF-1 expression (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, targeted disruption of the IRF-1 gene in mice results in reduced incidence and severity of collagen-induced arthritis (19). Recently, we have shown that IFNg induced IRF-1 gene expression in FRTL-5 rat thyroid cells (20). Taken together, IRF-1 may play a role in the pathogenesis of AITD.…”
Section: Introductionmentioning
confidence: 91%